Study of radiation attenuation ability of clay and cement mixture with added eggshell. (March 2020) - Jasmine, J N Z; Ramzun, M R; Zahirah, N A N; Azhar, A R; Hana, M Al-M; Zakiah, Y N; Yasmin, M R
Abstract: Concrete is a common material used to build physical barrier as protection against ionized radiation. However, excessive used of concrete may lead to increase volume on mining of cement and sand, thus contribute to catastrophic on nature. This project is done to find suitable material that can replace the usage of concrete in order to build physical barrier for radiation shielding. Hence, combination of Kaolin clay and eggshell powder are chosen as these materials are cheap, biodegradable and eco-friendly. Two main types of sample blocks are prepared: concrete and clay blocks. The portion of eggshell powder are varied, with increment of 1/10 cups for each sample. All samples are exposed on 60, 80 and 100 kVp of x-ray energy and absorbed dose were recorded. Results shows that blocks with adding eggshell powder contribute to greater value of radiation absorption ratio compared to blocks with non-added of eggshell powder. In addition, Sample 4 (consist of 4/10 cup of eggshell powder) were found to be the suitable portion due to optimum value were seen between these concrete and clay blocks. Hence, the clay blocks with additional of eggshell powder can be used to replace the usage of concrete for radiation shielding building.